MEMBANGUN KRISTOLOGI MELALUI SENI RUPA KRISTUS TERSALIB GAYA WAYANG PURWA - Bayu Edvra Paskalis (Jurnal Teologi (Journal of Theology), 2017)
After the Romantic period, visual art in the Catholic church tends to petrify its style. Realism is the apparent style acknowledged by the Church. Meanwhile, there are so many visual art styles emerged all around the world. One of these phenomena is the Crucified Christ in Wayang Purwa style, a Javanese-Christian hybrid that has been popular in the last two decades in its various forms. Wayang is experienced as a cultural identity by Javanese people, and therefore its visual art, the Wayang Purwa style, is also experienced as part of cultural identity. The Crucified Christ is the most popular example of the hybridization between this Javanese art and Christian theme. This is the object of the study. A contextual Christology shall be constructed from an experience of that object, in light of studies in Asian Christology. The result is a Javano-Christian image of the crucified Christ. Javanese people, who love delicate aestethics and ethics, understand Jesus Christ as a Javanese mystical Guru, a perfect harmony of humanity and divinity, and clothed as a pandhita. His frail and simple humanity embody his divinity which enables him to overcome his pain and sufferings on the cross.